1996
DOI: 10.1128/aac.40.5.1311
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of ceftriaxone (1,000 milligrams intravenously) in abdominal tissues during open prostatectomy

Abstract: Ceftriaxone concentrations in abdominal tissues were evaluated at different stages of open prostatectomy. Ceftriaxone was administered as antibiotic prophylaxis, and 15 consecutive patients were given a single dose of ceftriaxone (1,000 mg intravenously in 1 min) 30 min before surgery. Ceftriaxone concentrations in tissue were determined at three stages of the surgical procedure; upon the opening of the abdominal cavity, during the prostatectomy, and upon the closure of the abdominal cavity. Samples of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Interpretation of in vitro antibiotic susceptibility is based on achievable serum concentrations, which could differ from drug levels in the urine. Urine concentrations of ceftriaxone after a single 1000‐mg intravenous injection were three times higher than serum concentrations, and urine concentrations were tenfold greater than the minimum inhibitory concentration of 4 µg/g of tissue 5 . The high treatment success rate and the low UTI relapse rate in our study could be attributed to the initial intravenous G3C.…”
Section: Figurementioning
confidence: 52%
“…Interpretation of in vitro antibiotic susceptibility is based on achievable serum concentrations, which could differ from drug levels in the urine. Urine concentrations of ceftriaxone after a single 1000‐mg intravenous injection were three times higher than serum concentrations, and urine concentrations were tenfold greater than the minimum inhibitory concentration of 4 µg/g of tissue 5 . The high treatment success rate and the low UTI relapse rate in our study could be attributed to the initial intravenous G3C.…”
Section: Figurementioning
confidence: 52%
“…A review of the literature demonstrated that there are some reports that describe the measurement of cefuroxime and other cephalosporins in several biological matrices such as bone tissue, abdominal fat, and heart tissue [10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…To prevent infections after cardiac surgery, it is important to ensure the presence of adequate plasma concentrations of the antibiotic, thus permitting access of the drug to the site of highest bacterial exposure [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, before determination of tissue concentration, 100 mg of prostatic tissue was crushed with 1 milliliter of isotonic saline solution. This could have led to a wide spread of the tissue concentration [ 13 ]. Currently, micro-dialysis is used to counter this variation in determined tissue concentration; the reported values could be seen as estimates of the real value [ 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%